Spis treści [New Trends in Business Management / ed. by Joanna Radomska, Anna Witek-Crabb. - Wroclaw, 2024] - Radomska, Joanna. Redakcja; Witek-Crabb, Anna. Redakcja (Debiuty studenckie. New Trends in Business Management, 2024)
[Zeszyt zawiera dziewięć artykułów przygotowanych w języku angielskim, dotyczących aktualnych trendów w zarządzaniu. W prezentowanych opracowaniach szczegółowo opisano m.in. następujące zagadnienia: Motivation Systems Evolution and Their Impact on Employee Satisfaction in a Modern Workplace on the Example of IT Industry; Efficient Communication in Distributed Collaboration: A Study of Remote Work Environments; A Critical Analysis of Corporate Governance: The Case of BlackRock; Leadership Styles Identification – Case of the Company from an Industrial Installations Sector; Business Model Innovation Process on the Example of an IT Company] z zapowiedzi.
s. 135
Keywords: motivational system; types of organisations; Laloux's model; remote work; leadership